THE DOMINATION OF THE GOVERNMENT IN THE POLITICAL SYSTEM OF THE REPUBLIC OF MACEDONIA - Kuci, Driton (European Scientific Journal, ESJ, 2015)
The 1991 Constitution of the Republic of Macedonia inaugurated the system of division of powers as a fundamental value of the constitutional order. It abandoned the system of unity government (the assembly system), along with the one-party system, and substituted them with the multiparty parliamentary system. According to the principle of the division of powers, the power is divided into legislative, executive, and judicial (Article 8, item 4 of the Constitution of the Republic of Macedonia). The legislative authority is exercised by the Assembly; the executive is shared between the Government and the President; and the judicial power is exercised by the courts. Nevertheless, parliamentary democracy is not determined only by the constitutional framework, but also by the (un) democratic tradition, the model of political culture, as well as the electoral and party system. In this sense, the same normative model works differently in different countries or at different periods of the development of the same political system. This is especially evident in the relations between parliament and government. The dominance of the executive is not only a characteristic of the model of organization of power in the Republic of Macedonia, but it is also a global tendency. In this sense, the parliament of the Republic of Macedonia shares the ‘fate’ of the representative bodies in contemporary parliamentarism. However, in the absence of a democratic tradition, the presence of subject political culture, the strong elements of partocracy and the party state, the fragile and fragmented civil society, and the weak general public, gives dramatic dimensions to the dominance of the executive over the legislative power.